Vaccination with short-term-cultured autologous PBMCs efficiently activated STLV-1-specific CTLs in naturally STLV-1-infected Japanese monkeys with impaired CTL responses - Hasegawa, Atsuhiko; Murata, Megumi; Fujikawa, Tomoka; Katagiri, Kuniko; Nagano, Yoshiko; Masuda, Takao; Kuramitsu, Madoka; Nakajima, Shinsuke; Fujisawa, Jun-ichi; Okuma, Kazu; Grover, Poonam; Kidiga, Maureen; et al. (PLoS pathogens, 2023)
A small proportion of human T-cell leukemia virus type-1 (HTLV-1)-infected individuals develop adult T-cell leukemia/lymphoma, a chemotherapy-resistant lymphoproliferative disease with a poor prognosis. HTLV-1-specific cytotoxic T lymphocytes (CTLs), potential anti-tumor/virus effectors, are impaired in adult T-cell leukemia/lymphoma patients. Here, using Japanese monkeys naturally infected with simian T-cell leukemia/T-lymphotropic virus type-1 (STLV-1) as a model, we demonstrate that short-term-cultured autologous peripheral blood mononuclear cells (PBMCs) can serve as a therapeutic vaccine to activate such CTLs. In a screening test, STLV-1-specific CTL activity was detectable in 8/10 naturally STLV-1-infected monkeys. We conducted a vaccine study in the remaining two monkeys with impaired CTL responses. The short-term-cultured PBMCs of these monkeys spontaneously expressed viral antigens, in a similar way to PBMCs from human HTLV-1 carriers. The first monkey was subcutaneously inoculated with three-day-cultured and mitomycin C (MMC)-treated autologous PBMCs, and then boosted with MMC-treated autologous STLV-1-infected cell line cells. The second monkey was inoculated with autologous PBMC-vaccine alone twice. In addition, a third monkey that originally showed a weak STLV-1-specific CTL response was inoculated with similar autologous PBMC-vaccines. In all three vaccinated monkeys, marked activation of STLV-1-specific CTLs and a mild reduction in the STLV-1 proviral load were observed. Follow-up analyses on the two monkeys vaccinated with PBMCs alone indicated that STLV-1-specific CTL responses peaked at 3–4 months after vaccination, and then diminished but remained detectable for more than one year. The significant reduction in the proviral load and the control of viral expression were associated with CTL activation but also diminished 6 and 12 months after vaccination, respectively, suggesting the requirement for a booster. The vaccine-induced CTLs in these monkeys recognized epitopes in the STLV-1 Tax and/or Envelope proteins, and efficiently killed autologous STLV-1-infected cells in vitro . These findings indicated that the autologous PBMC-based vaccine could induce functional STLV-1-specific CTLs in vivo .